2019
DOI: 10.1016/j.foodchem.2018.07.080
|View full text |Cite
|
Sign up to set email alerts
|

One-step process for producing prebiotic arabino-xylooligosaccharides from brewer's spent grain employing Trichoderma species

Abstract: Xylooligosaccharides (XOS) are prebiotic nutraceuticals that can be sourced from lignocellulosic biomass, such as agro-residues. This study reports for the first time an optimization study of XOS production from agro-residues by direct fermentation using two Trichoderma species. A total of 13 residues were evaluated as potential substrates for single-step production. The best results were found for Trichoderma reesei using brewers' spent grain (BSG) as substrate. Under optimal conditions (3 days, pH 7.0, 30 °C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 43 publications
1
43
0
1
Order By: Relevance
“…The brewer's spent grains (BSG) were kindly supplied by Super Bock Group (Portugal). This residue contains 22.3 ± 0.6% (w/ w) of insoluble lignin, 4.7 ± 0.3% (w/w) of acid soluble lignin, 16.9 ± 0.4% (w/w) of extractives (which include non-structural sugars, inorganic material, nitrogenous material, among others), 19.2 ± 0.5% (w/w) of proteins, 17.5 ± 0.3% (w/w) of cellulose, 4.54 ± 0.04% (w/w) of ashes and 16.5 ± 0.7% (w/w) of arabinoxylan with 10.3 ± 0.2% (w/w) of xylose (Amorim et al, 2018). This chemical composition is in accordance to Vieira et al (2014), who used BSG obtained from the same brewery.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The brewer's spent grains (BSG) were kindly supplied by Super Bock Group (Portugal). This residue contains 22.3 ± 0.6% (w/ w) of insoluble lignin, 4.7 ± 0.3% (w/w) of acid soluble lignin, 16.9 ± 0.4% (w/w) of extractives (which include non-structural sugars, inorganic material, nitrogenous material, among others), 19.2 ± 0.5% (w/w) of proteins, 17.5 ± 0.3% (w/w) of cellulose, 4.54 ± 0.04% (w/w) of ashes and 16.5 ± 0.7% (w/w) of arabinoxylan with 10.3 ± 0.2% (w/w) of xylose (Amorim et al, 2018). This chemical composition is in accordance to Vieira et al (2014), who used BSG obtained from the same brewery.…”
Section: Methodsmentioning
confidence: 99%
“…Brewers' spent grain (BSG) represents the most abundant lignocellulosic by-product of the brewing industry (Steiner, Procopio, & Becker, 2015) and it has been used as raw material for the production of arabino-xylooligosaccharides (AXOS) (Coelho, Rocha, Saraiva, & Coimbra, 2014). We previously found that a single step bioprocess to produce AXOS through the direct fermentation of BSG by Trichoderma strains (Amorim, Silvério & Rodrigues, 2018). Despite the undeniable advance of using an integrated process for XOS production, a considerably high production time (3 days) was reported.…”
Section: Introductionmentioning
confidence: 99%
“…Amorim et al [26] demonstrated the XOS production from brewers spent grain (BSG) by direct fermentation using Trchoderma strains in single step process.…”
Section: Xos Production By Enzymatic Methodsmentioning
confidence: 99%
“…During the HPLC analysis the produced XOS were separated and individually collected according to their DP for chemical characterization analysis (Section 2.9). The DP of the XOS was estimated by TLC, as described by Amorim, Silvério, and Rodrigues, (2019), and confirmed by HPLC (Section 2.9) and GC-MS (Section 2.10). The XOS yield, Y XOS (mg/g) was defined as the ratio between the total concentration of XOS (mg) and the mass of xylan (g) used in the fermentation.…”
Section: Xos Quantificationmentioning
confidence: 99%
“…To minimize the salt interference in the HPLC analysis, XOS produced by fermentation of xylan under optimal conditions were treated with activated charcoal as described in Amorim et al (2019). The supernatant was collected (20 mL), centrifuged and loaded onto 13 g of activated charcoal.…”
Section: Partial Purification Of Xos Produced By Direct Fermentationmentioning
confidence: 99%